PENERAPAN PRINSIP-PRINSIP SERVQUAL DALAM MENINGKATKAN KUALITAS PELAYANAN PEMERINTAHAN - Luthfi Natsir; Pandji Santoso; Tati Sarihati (Universitas Wiralodra, 2026)
This study aims to analyze the application of SERVQUAL principles in public services in Indonesia through a literature review method. Data was collected by reviewing various national and international scientific articles indexed in Scopus and other reputable journals to identify gaps, developments, and practices in public service quality. The results of the analysis show: 1) tangibles emphasize the importance of modernizing facilities and infrastructure, 2) reliability focuses on the digitization of services, 3) responsiveness concerns accelerating response times through the use of technology, 4) assurance emphasizes improving competence and transparency of procedures, and 5) empathy highlights the importance of personal communication and humanistic attention. This study concludes that the application of SERVQUAL provides a comprehensive framework for understanding public service quality, while offering theoretical implications for the development of science and practical implications in the form of strategies to strengthen government services oriented toward public satisfaction. The limitation of this study lies in its literature-based nature, so further research is recommended to conduct empirical testing involving broader and more in-depth field data.